Provocation and related subjective experiences along the dark tourism spectrum. Issue 6 (1st November 2020) - Lacanienta, Andrew; Ellis, Gary; Hill, Brian; Freeman, Patti; Jiang, Jingxian
ABSTRACT: We examined relations between 'darkness' of dark tourism sites, provocation, and select indicators of the quality of visitors' immediate subjective experiences. Experience observations ( N  = 101) were collected from tourists who visited Auschwitz (Krakow), Schindler's Factory (Krakow), Execution Square (Paris), and a ghost tour (Edinburgh). Research participants completed measures of provocation and quality of experience at the end of their visits to each site. Hypotheses were founded in four theories: self-determination theory, cognitive dissonance theory, arousal theory, and the theory of structured experience. These hypotheses proposed that particular experience outcomes vary according to the 'darkness' of the dark tourism site. Results show lighter dark tourism experiences (execution square and the ghost tour) were more affectively pleasing and yielded a significantly stronger sense of agency (inclination to act) than darker sites. Darker dark tourism experiences (Auschwitz and Schindler's Factory) were more provocative, valued, meaningful, and likely to be recommended.